1997
DOI: 10.1177/089198879701000404
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Predictors of Adaptive Kitchen Behavior in Geriatric Psychiatry Inpatients

Abstract: This study examined the degree to which demographic variables, psychiatric diagnosis, depression rating, and neuropsychological test performance predict adaptive kitchen behavior in geriatric psychiatry patients and normal elderly volunteers. Amixed group of 27 participants including 8 normal volunteers and 19 geriatric psychiatry inpatients underwent psychiatric evaluation, neuropsychological testing, and a kitchen skills assessment conducted in a natural setting. Both depression and dementia were prevalent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In general, correlations between the neuropsychological measures and the global measure of daily functioning, the OTDL-R, are consistent with previous studies indicating that neuropsychological measures are good predictors of daily function in older adults (Benedict et al, 1997;Cahn-Weiner et al, 2000;Farias et al, 2003;Freilich & Hyer, 2007;Glosser et al, 2002;Hill et al, 1995;Perry & Hodges, 2000;Richardson et al, 1995;Royall et al, 2004). The size of the correlations ranged from .39 to .59, representing medium to large effects (Cohen, 1992).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, correlations between the neuropsychological measures and the global measure of daily functioning, the OTDL-R, are consistent with previous studies indicating that neuropsychological measures are good predictors of daily function in older adults (Benedict et al, 1997;Cahn-Weiner et al, 2000;Farias et al, 2003;Freilich & Hyer, 2007;Glosser et al, 2002;Hill et al, 1995;Perry & Hodges, 2000;Richardson et al, 1995;Royall et al, 2004). The size of the correlations ranged from .39 to .59, representing medium to large effects (Cohen, 1992).…”
Section: Discussionsupporting
confidence: 88%
“…The performance of individuals with dementia on an overlapping figures task significantly contributed to the prediction of ADLs (Hill, Backman, & Fratiglioni, 1995). Benedict, Goldstein, Dobraski, and Tannenhaus (1997) reported that a measure of visuospatial function contributed to the prediction of a kitchen task in a mixed sample composed mostly of geriatric psychiatry inpatients. In a sample of individuals early in the course of Alzheimer's disease (AD), visuospatial function was "the sole cognitive predictor" of functional ability (Perry & Hodges, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to direct IADL performance assessment and self-report or proxy reports, research has shown that neuropsychological test performance can predict IADL performance in older adults with and without dementia and psychiatric disorders. Benedict, Goldstein, Dobraski, and Tannenhaus (1997) found that visuospatial tasks could be good predictors of IADL performance. However, Shallice and Burgess (1991) reported that individuals with frontal lobe damage performed within the normal range on neuropsychological tests and laboratory tasks presumed to rely on executive functions.…”
mentioning
confidence: 94%
“…A complete neuropsychological examination is required to identify each patient's deficits and preserved cognitive functions. Visuospatial tasks are claimed to be "more predictive of instrumental activities of daily living than are cognitive tasks emphasising verbal and memory activities" (Benedict, Goldstein, Dobraski, & Tannenhaus, 1997), and so patients should be tested on both kinds of tasks. Even so, a "psychometric" cognitive evaluation is likely to prove insufficient, because of the lack of ecological validity of this kind of assessment, which generally does not reveal the patient's difficulties with real-life activities: "neuropsychological functioning is moderately predictive of functional status" (Farias, Harrell, Neumann, & Houtz, 2003).…”
Section: Introductionmentioning
confidence: 99%